Impaired Whole-Blood Fibrinolysis is a Predictor of Mortality in Intensive Care Patients - Brewer, Julie S.; Hvas, Christine L.; Hvas, Anne-Mette; Larsen, Julie B. (TH Open, 2024)
Background Altered fibrinolysis is considered to play a crucial role in the development of coagulopathy in sepsis. However, routine laboratory tests for fibrinolysis are currently very limited, and the impact of fibrinolytic capacity on clinical outcome is poorly investigated.Objectives To assess whole-blood fibrinolysis in patients admitted to the intensive care unit (ICU) and compare fibrinolysis in sepsis patients with nonsepsis patients. Further, to investigate associations between fibrinolytic capacity and 30-day mortality and venous thromboembolism (VTE).Methods This study was designed as a prospective cohort study. Adult ICU patients were included at the Aarhus University Hospital, Denmark. All patients had a blood sample obtained the morning after admission. A modified thromboelastometry (ROTEM®) analysis with tissue plasminogen activator (ROTEM®-tPA) was used to assess fibrinolysis. The primary endpoint was difference in ROTEM®-tPA lysis time between sepsis patients and nonsepsis patients.Results ROTEM®-tPA revealed fibrinolytic impairment in sepsis patients (n = 30) compared with nonsepsis ICU controls (n = 129), with longer lysis time (median [interquartile range] 3,600 [3,352–3,600] vs. 3,374 seconds [2,175–3,600], p < 0.01), lower maximum lysis (23 [8–90] vs. 94% [14–100], p = 0.02), and lower fibrinolysis speed (0.41 [0.0–1.4] vs. 1.6 mm/min [0.1–2.7], p = 0.01). In the composite ICU population, 61% (97/159) demonstrated prolonged lysis time indicating impaired fibrinolytic capacity. These patients had higher 30-day mortality (adjusted odds ratio [OR]: 2.26 [0.83–6.69]) and VTE risk (OR: 3.84 [0.87–17.8]) than patients with normal lysis time.Conclusion Sepsis patients showed impaired fibrinolysis measured with ROTEM®-tPA compared with nonsepsis patients and ROTEM®-tPA lysis time was associated with 30-day mortality and VTE in the entire ICU cohort.
Keywords: blood coagulation tests; critical care; fibrinolysis; sepsis; thromboelastography